HUBUNGAN KECERDASANÂ EMOSI TERHADAP HASIL BELAJAR LAY-UP BOLA BASKET STUDI PADA SISWA KELAS XI IPA 5 SMA NEGERI 2 NGANJUK - SETYA ANGGARA, DANANG (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In formal education the intellectual intelligence is not the one and only basis for assessment of learning succes. In addition to intellectual intelligence, the role of emotional intelligence is also critical to achieve student succes in a learning and give student the ability to learn well, so it has a good succesful rate of learning as well. Purpose of this research is to determine whether there is a relationship between emotional intelligence and learning succes lay-up basketball or not. This type of research is descriptive quantitative related to variables that are correlational. The research instrument in the form of a questionnarie/poll tests of emotional intelligence with agencies EXENSIA psychology as a cooperating agency in the manufacturing test of emotional intelligence (Emotional Quotient) and right side lay-up test. The result are tested by using product moment correlation analysis. The subjects of the research were student of class XI, 2 Senior High School  Nganjuk with a population of 356 students. The sample in this study was determined by using cluster random sampling technique where researchers draw randomly from ten classes and selected class XI Science 5 with 36 students. Based on the calculation of the product moment correlation, it was found that the relationship between emotional intelligence and learning outcomes basketball lay-up class XI Science 5, 2 Senior High School Nganjuk is counted rcounted(0,672)>rtable(0,329) using a significance level of 5%. While the coefficient of determination 45,16 this means that the contribution of emotional intelligence variables on learning outcomes basketball lay-up class XI Science 5, 2  Senior High School Nganjuk is to 45,16%. From the calculation of the data analysis it can be concluded that there is a significant relationship between emotional intelligence and the learning outcomes of a basketball lay-up class XI Science 5, 2  Senior High School Nganjuk. Keywords: Emotional intelligence (Emotional Quotient), Learning outcomes, Basketball lay-up.